Allochroic‐Graphene Oxide Linked 3D Oriented Surface Imprinting Strategy for Glycoproteins Assays. (13th August 2018) - Chen, Guosheng; Kou, Xiaoxue; Huang, Siming; Huang, Shuyao; Zhang, Rui; Liu, Chao; Shen, Jun; Zhu, Fang; Ouyang, Gangfeng
Abstract: Affordable methodologies for screening of disease‐related biomarkers are vital for early clinical diagnosis, and can potentially improve the survival rate. Herein, a cost‐efficient and easy‐to‐use approach, called allochroic‐graphene oxide linked oriented surface imprinting strategy (AGO‐OSI), is imparted for rapid glycoproteins screening with naked eyes. The novel detection principle herein relies on the boronate‐affinity sandwich‐like assembly, in which the target glycoproteins are specifically captured by the engineered 3D oriented surface imprinting magnetic microprobe, and followed by labeling with the pH‐triggered allochroic‐graphene oxide. Compared with the enzyme‐linked immunosorbent assay, no antibody‐assisted recognition or complicated enzymatic labeling is required, endowing the AGO‐OSI with the merits of low‐cost, labor‐saving, and user‐friendly. In addition, the pH‐triggered allochroic‐graphene oxide provides a simple, real‐time, and economical signal readout, without the sophisticated instruments requirement. Finally, it is successfully applied to rapid diagnosis of α‐fetoprotein (AFP) in liver cancer event with naked eyes, further manifesting the superiority of AGO‐OSI. It is believed that the cost‐efficient and easy‐to‐use strategy proposed herein can potentially be a versatile tool for point‐of‐care diagnosis, especially applicable in resource‐constrained regions. Abstract : An appealing allochroic‐graphene oxide linked 3D oriented surface imprinting strategy is proposed for assaying glycoproteins with the naked eye. The innovative sandwich‐like pattern provides high specificity, strong recognition affinity, and fast labeling speed, without requiring antibodies or enzymes. The limitations of conventional enzyme‐linked immunosorbent assays are circumvented by this cost‐efficient, labor‐saving, and user‐friendly approach.